Dynamic Shock Cushioning Characteristics and Vibration Transmissibility of X-PLY Corrugated Paperboard - Yanfeng Guo; Wencai Xu; Yungang Fu; Hongtao Wang (Shock and Vibration)
X-PLY corrugated paperboard is a new-type corrugated paperboard with three layers of orthotropic corrugated sandwiches structure, and may be employed to protect products from shock or vibration damage during distribution. This article deals with the characterization of properties of X-PLY corrugated paperboard relevant to its application for protective packaging in distribution, such as dynamic cushioning curves, vibration transmissibility and frequency curves. The main feature of article is the evaluation on the dynamic shock cushioning characteristics and vibration transmissibility of X-PLY corrugated paperboards by a series of experimental studies on the drop shock tester and vibration tester, the establishment of experimental formulas of dynamic cushioning curves, and the analysis of peak frequencies, vibration transmissibility and damping ratios. By using the fitting polynomial of curve and method of the least mean square, the experimental formulas and characteristic coefficients of dynamic cushioning curves have been obtained. From the vibration tests with slow sine sweep, the peak frequencies and vibration transmissibility are measured and used to estimate the damping ratios. These works provide basic data and curves relevant to its application for protective packaging in distribution.